Mesangial Cells Exhibit Features of Antigen-Presenting Cells and Activate CD4+ T Cell Responses. (17th June 2019) - Yu, Hongyu; Cui, Shaoyuan; Mei, Yan; Li, Qinggang; Wu, Lingling; Duan, Shuwei; Cai, Guangyan; Zhu, Hanyu; Fu, Bo; Zhang, Li; Feng, Zhe; Chen, Xiangmei
Abstract : Background. Mesangial cells play a prominent role in the development of inflammatory diseases and autoimmune disorders of the kidney. Mesangial cells perform the essential functions of helping to ensure that the glomerular structure is stable and regulating capillary flow, and activated mesangial cells acquire proinflammatory activities. We investigated whether activated mesangial cells display immune properties and control the development of T cell immunity. Methods. Flow cytometry analysis was used to study the expression of antigen-presenting cell surface markers and costimulatory molecules in mesangial cells. CD4+ T cell activation induced by mesangial cells was detected in terms of T cell proliferation and cytokine production. Results. IFN- γ -treated mesangial cells express membrane proteins involved in antigen presentation and T cell activation, including MHC-II, ICAM-1, CD40, and CD80. This finding suggests that activated mesangial cells can take up and present antigenic peptides to initiate CD4+ T cell responses and thus act as nonprofessional antigen-presenting cells. Polarization of naïve CD4+ T cells (Th0 cells) towards the Th1 phenotype was induced by coculture with activated mesangial cells, and the resulting Th1 cells showed increased mRNA and protein expression of inflammation-associated genes. Conclusion. Mesangial cells can present antigen and modulate CD4+ T lymphocyte proliferation and differentiation. Interactions between mesangial cells and T cells are essential for sustaining the inflammatory response in a variety of glomerulonephritides. Therefore, mesangial cells might participate in immune function in the kidney.